The Existing Problems and Solutions of Cultural Product Innovation and the Development of Urban Brand Characteristics - Wang, Shuang; Wei, Baotao (Transactions on Economics, Business and Management Research, 2023)
In order to promote the core socialist values, enhance national confidence, and enhance cultural pride, the state vigorously advocates the development of the cultural industry and promotes the development and design of cultural and creative products. Cultural and creative products themselves have multiple functions such as urban cultural dissemination, urban brand building, urban image establishment, and urban economic development, achieving better utilization of cultural and creative product functions and driving urban economic development. This article mainly selects the design case of tourism cultural and creative products in Shenyang to analyze the current problems, such as scattered urban image, lack of visual symbols in brand image, and slow digital development. Corresponding solutions are proposed, hoping to provide reference for the innovation of cultural and creative products in Liaoning and the development of Shenyang's urban brand image.